2015
DOI: 10.1515/amm-2015-0064
|View full text |Cite
|
Sign up to set email alerts
|

Low Frequency Mechanical Spectroscopy Study of Three Pyrrolidinium Based Ionic Liquids

Abstract: In this work we present our recent results on three ionic liquids (ILs), which share bis(trifluoromethanesulfonyl)imide (TFSI) as anion and have different pyrrolidinium based cations. By means of a combination of mechanical spectroscopy and thermal analysis, many of the physical processes occurring during cooling down from the liquid phase, can be studied. Depending both on the diverse cation and the different thermal history, crystallization from the melt or glass transition, cold-crystallization, solid-solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 11 publications
(18 reference statements)
2
19
0
Order By: Relevance
“…We already reported the comparison of DSC and DMA measurements both on pure ionic liquids and on an ionic liquid swelling a polymer membrane. We showed that DMA is a powerful tool to identify the temperatures of solidification and liquefaction of IL and to study the kinetics of these phase transitions [21,27]. In fact an increase of M is expected in correspondence with the solidification, while a strong decrease of M on heating indicates the liquefaction.…”
Section: The Solid-liquid Phase Transitionmentioning
confidence: 93%
See 2 more Smart Citations
“…We already reported the comparison of DSC and DMA measurements both on pure ionic liquids and on an ionic liquid swelling a polymer membrane. We showed that DMA is a powerful tool to identify the temperatures of solidification and liquefaction of IL and to study the kinetics of these phase transitions [21,27]. In fact an increase of M is expected in correspondence with the solidification, while a strong decrease of M on heating indicates the liquefaction.…”
Section: The Solid-liquid Phase Transitionmentioning
confidence: 93%
“…Dynamic mechanical analysis (DMA) measurements were conducted by means of a Perkin Elmer DMA8000 equipped with a liquid nitrogen cooling system and the material pocket accessory, in order to determine the solidification/liquefaction temperature [20,21]. The sample was spread into a stainless steel material pocket with dimensions of 30 mm by 14 mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic mechanical analysis was carried out using a PerkinElmer DMA 8000 instrument, following a procedure already used by us in previous works 2,7,8 : the sample, which is liquid at room temperature, was laid out into a stainless steel Material Pocket, supplied by PerkinElmer, with dimensions of 30.0 mm by 14.0 mm by 0.5 mm; the pocket, which is scored in the mid-point, was then folded in half and crimped closed to form a sandwich. Flexural vibration measurements were performed in the three-point bending configuration.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, in pyrrolidinium based ILs, depending both on the ions composition of the material and the different thermal history, crystallization from the melt or glass transitions, cold-crystallization and solid-solid phase transitions were observed and the kinetics of the crystallization processes was studied in the framework of the Johnson-Mehl-Avrami-Kolmogorov theory 7 ; the Avrami parameters, namely the activation energy and the Avrami index, were derived by the measure of the modulus variation under isothermal and non-isothermal conditions for both the crystallization from the melt and the cold crystallization observed on heating, thus providing additional information with respect to the common calorimetric measurements 7 .…”
Section: Introductionmentioning
confidence: 99%